Fluorine-18 fluorodeoxyglucose avid thyroid incidentalomas on PET/CT scan in cancer patients: how sinister are they?. Issue 10 (October 2016) - Hassan, Aamna; Riaz, Saima; Zafar, Waleed
Abstract : Objective: To evaluate the prevalence of malignancy in incidental thyroidal uptake on PET with fluorine-18 deoxyglucose integrated with computed tomography ( 18 F-FDG PET/CT) in Pakistani cancer patients and to assess the role of standardized uptake value (SUV) in deciding which lesions to investigate further. Method: We retrospectively reviewed all patients who underwent 18 F-FDG PET/CT scans over a period of 59 months and further analysed those with visually increased thyroidal uptake. Uptake was classified as focal or diffuse. Results: Out of 10 012 18 F-FDG PET/CT scans done for evaluation of known, nonthyroid malignancies, 173 (1.7%) showed incidental thyroid uptake. Of these, 29 were malignant (33%; 24 focal, five diffuse) and 58 were benign (67%; 26 focal, 32 benign) cases. The prevalence of malignancy was significantly higher in cases of focal uptake ( P =0.002). After controlling for sex, age, and SUV those with focal uptake were 6.5 times more likely to have malignancy compared with those with diffuse uptake. Odds ratio 6.5; 95% confidence interval 2.0–20.9; P less than 0.01. We found no correlation of SUV with the incidence or type of malignancy. Conclusion: Focal thyroid uptake on 18 F-FDG PET/CT imaging should be sonographically correlated and if indicated with cytological analysis. Although diffuse uptake is usually benign, lymphoma is the leading malignant differential. Nonavid lesions have a low likelihood of malignancy.